(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
This article focuses on the importance of practical social work today. Today it is difficult to achieve a high result without studying and analyzing foreign experience, no matter which sphere. The fact that in the XXI century the number of the world’s population is increasingly shooting, and at this time various social problems are growing, requires bartarfing this problem and creating the necessary conditions for the population. It is in solving social problems that the practical significance of work social work is revealed in the article.